Upaya Meningkatkan Kemampuan Membaca Al-Qur’an Melalui Program Tahsin Al-Qur’an Pada Bidang Studi Al-Qur’an Hadits Siswa Kelas VIII MTs Swasta Teladan Gebang - Irma Melati, Kamaliah, Khairuddin (Pusdikra-Publishing.com, 2022)
Support from the management of Madrasahs to implement the Tahsin Qur'an Program in learning activities in the field of Al-Qur'an Hadith studies is highly expected for the continuity and smoothness of student learning activities at Exemplary Private MTs Gebang because without the implementation of the Tahsin Qur'an Program which is innovation and learning creativity, the teaching and learning activities will not run as expected. Based on the background of the problem above, the researcher is interested in conducting research that discusses the ability to read the Qur'an through the Tahsin Qur'an Program in the field of Al-Qur'an Hadith studies in Madrasahs. The method used in this research is Classroom Action Research. The formulation of the problem in this study is: How is the ability to read the Qur'an of students at Teladan Gebang Private MTs? How is the implementation of the Qur'an Tahsin Program in the field of Al-Qur'an Hadith students of Gebang Exemplary Private MTs? What are the efforts to improve the ability to read the Koran through the Tahsin Qur'an Program in the field of Al-Qur'an Hadith students at Model Gebang Private MTs? The conclusions in this study are: The ability to understand Al-Qur'an Reading material by class VIII students of MTs Teladan Gebang has increased by using the Al-Qur'an Tahsin Program strategy from the conclusions of the data obtained, namely: In the pre-cycle completeness reached 54% of students or as many as 6 students who have completed and 24 students have not completed. In cycle I, the percentage of completeness was achieved at 61.8% or as many as 11 students who completed and 19 students who had not completed. In cycle II, the percentage of learning completeness was achieved by 78% or as many as 23 students had completed and 7 students had not completed. In cycle III, learning mastery was achieved at 100%, an increase of 89.66 from cycle II. Or as many as 30 students get completeness in learning Al-Qur'an reading material. Thus, it can be concluded that the use of the Al-Qur'an Tahsin method can increase students' ability to read the Al-Qur'an.